Method for remarkably regulating and controlling spin-orbit torque based on magnetic phase change material iron-rhodium alloy
By using magnetic phase change material iron-rhodium alloy in spin electronics devices and using temperature to drive its magnetic phase transformation, efficient regulation of spin orbit torque efficiency and fully electronically controlled perpendicular magnetic moment flip are achieved, and the existing technology is solved The difficulty of magnetization flip of medium SOT devices under the condition of no in-plane auxiliary magnetic field and the problem of constant SOT efficiency.
Patent Information
- Application Number
- CN202411468793.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-14
AI Technical Summary
The existing spin orbit torque (SOT) devices are difficult to achieve deterministic magnetization flip without in-plane auxiliary magnetic field conditions, and the SOT efficiency remains unchanged in a single sample, and there is a lack of effective regulation methods.
The magnetic phase change material iron-rhodium alloy is used as the spin source layer, and the perpendicular magnetized heterojunction of the iron-rhodium alloy layer/non-magnetic light metal layer/ferromagnetic layer/covering layer is formed, and the temperature is used to drive the iron-rhodium alloy to generate antiferromagnetism. -First-order phase transformation of ferromagnetics achieves efficient regulation of spin orbit torque.
Achieve significant regulation of spin orbit torque efficiency (up to 450%), and fully electronically controlled perpendicular magnetic moment flip without an external auxiliary magnetic field, reducing the power consumption of the device and promoting the integration and practicality of SOT devices. change.
Smart Images

Figure CN119451548A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of spin electronics, and more specifically, relates to a method for achieving significant regulation of spin-orbit torque based on a magnetic phase change material iron-rhodium alloy. Background Art
[0002] The core of spin electronics is to use electric current to achieve effective regulation of magnetic moment, and the realization of all-electrical control of magnetic moment has become a prerequisite for almost all modern scalable magnetic storage and logic devices. Among them, the spin orbit torque (SOT) effect, which uses the spin properties of electrons to achieve efficient reversal of magnetic moment, has attracted widespread attention from researchers. It can not only drive magnetic moment reversal and realize information storage, but also its related devices have the characteristics of high storage unit integration, high read and write speed, high read and write times and low power consumption. It has now become a research hotspot in the field of spin electronics and a mainstream technology for the new generation of spin electronics devices.
[0003] The basic structure of the spin-orbit torque device is a spin current source / ferromagnetic vertical heterojunction. For the SOT device, when a charge flow is introduced into the device, a spin polarization σ in the y direction will be generated. y , only in σ y The generated spin-orbit torque τ DL and τ FL It is impossible to achieve deterministic magnetization reversal under the action of the in-plane auxiliary magnetic field. An auxiliary magnetic field must be applied along the current direction to break the z-space symmetry of the magnetic moment of the ferromagnetic layer, thereby achieving a deterministic and repetitive magnetization reversal. However, the additional in-plane auxiliary magnetic field will increase the energy consumption of the device and is not conducive to the integration of SOT devices. Therefore, how to achieve SOT-induced magnetization reversal without an in-plane auxiliary magnetic field, that is, fully electrically controlled perpendicular magnetic moment reversal, is the focus of current spin electronics research.
[0004] In addition, given the importance of SOT and the important role played by related phenomena in the research and development of spin electronics, it is necessary to find a nanostructured spin with high SOT efficiency ξ SOT The materials that can realize electrically controlled field-free reversal are of great research significance. Based on this, the researchers proposed the following method to obtain high ξ SOT For example, by changing the composition / thickness / crystal structure of the heavy metal layer, the magnetic or oxidized non-magnetic metal layer, and controlling its oxygen content, different material systems can be obtained to achieve the desired effect. SOT The regulation of SOT Although the above methods can be used to SOTThe regulation effect of SOT is significant, but they all need to be realized in different material systems. The above regulation methods will introduce many uncontrollable factors from the outside world and do not take advantage of the practical application of SOT functional devices. On the other hand, achieving efficient regulation of SOT efficiency in a single sample is of great significance for the application of future devices. However, for a specific device composed of a certain material system, its SOT efficiency is almost fixed. Therefore, it is very important to seek a special material system to obtain high ξ SOT It is of great practical value to realize fully electrically controlled vertical magnetic moment reversal at the same time. Summary of the invention
[0005] In view of the above defects or improvement needs of the prior art, the purpose of the present invention is to provide a method for achieving significant regulation of spin-orbit torque based on the magnetic phase change material iron-rhodium alloy, wherein by using iron-rhodium alloy as a spin source layer to form a perpendicular magnetization heterojunction of iron-rhodium alloy layer / non-magnetic light metal layer / ferromagnetic layer / covering layer, efficient regulation of spin-orbit torque can be achieved (especially significant regulation of spin-orbit torque of up to 450%).
[0006] To achieve the above object, according to one aspect of the present invention, a heterojunction based on a magnetic phase change material iron-rhodium alloy is provided, which has a Hall target structure and is characterized in that it includes a magnetic phase change material iron-rhodium alloy layer and a non-magnetic light metal layer, a ferromagnetic layer and a covering layer stacked in sequence from bottom to top on the iron-rhodium alloy layer, wherein the ferromagnetic layer has a perpendicular magnetic anisotropy characteristic;
[0007] The iron-rhodium alloy layer serves as a spin source layer, and the magnetic phase change material iron-rhodium alloy can undergo an antiferromagnetic-ferromagnetic first-order phase transition as the temperature changes.
[0008] As a further preferred embodiment of the present invention, the non-magnetic light metal layer is a Ti layer;
[0009] Preferably, the thickness of the iron-rhodium alloy layer is 4 to 6 nm.
[0010] As a further preferred embodiment of the present invention, the material used for the ferromagnetic layer includes Co 20 Fe 60 B 20 、Co 40 Fe 40 B 20 、Co 60 Fe 20 B 20 Any one of .
[0011] As a further preferred embodiment of the present invention, the covering layer is any one of a MgO / SiN stack, a MgO / Ta stack, and a MgO / SiO2 stack, and the MgO layer in the stack is closer to the iron-rhodium alloy layer than the other layer.
[0012] According to another aspect of the present invention, the present invention provides a method for regulating the spin-orbit torque of the heterojunction constructed based on the magnetic phase change material iron-rhodium alloy, characterized in that a charge flow is introduced into the spin source layer, and the magnetic phase change material iron-rhodium alloy undergoes an antiferromagnetic-ferromagnetic first-order phase transition by changing the temperature;
[0013] When the temperature makes the magnetic phase change material iron-rhodium alloy in the antiferromagnetic state, the spin-orbit torque efficiency ξ SOT Higher;
[0014] When the temperature makes the magnetic phase change material iron-rhodium alloy in the ferromagnetic state, the spin-orbit torque efficiency ξ SOT Smaller.
[0015] As a further preferred embodiment of the present invention, the temperature variation range is 200K to 400K.
[0016] As a further preferred embodiment of the present invention, the spin-orbit torque efficiency ξ is SOT The higher value is ξ SOT_higher , spin-orbit torque efficiency ξ SOT The smaller value is ξ SOT_lower , then (ξ SOT_higher -ξ SOT_lower ) / ξ SOT_lower Not less than 450%.
[0017] Compared with the prior art, the above technical solution conceived by the present invention can achieve the following beneficial effects:
[0018] (1) The present invention forms a perpendicular anisotropic heterojunction of iron-rhodium alloy layer / non-magnetic light metal layer / ferromagnetic layer / covering layer by stacking a non-magnetic light metal layer, a ferromagnetic layer and a covering layer in sequence from bottom to top on the iron-rhodium alloy layer of magnetic phase change material.
[0019] The prior art knows that the magnetic phase change material iron-rhodium alloy (in the standard composition binary alloy FeRh, the Fe element and the Rh element each account for 50atom%; of course, the prior art has reported binary iron-rhodium alloys with other atomic proportions, and their phase change behaviors will be slightly different, but as long as they all behave as magnetic phase change materials, the spin-orbit efficiency can be regulated, but the regulation range will be slightly different) undergoes an antiferromagnetic-ferromagnetic first-order phase transition as the temperature rises (the phase transition temperature is about 350K), and it has a CsCl structure, such as Figure 1As shown in Figure 2, as the temperature rises from room temperature to about 350K, a first-order magnetic phase transition from antiferromagnetic phase to ferromagnetic phase can occur. During this phase transition, the resistance decreases and the magnetization increases (as shown later in the paper). Figure 3 as shown), and coupling with structural and electronic degrees of freedom.
[0020] (2) Furthermore, based on the present invention, the temperature-driven magnetic phase transition of the iron-rhodium alloy can be used to significantly control the spin-orbit torque of the system, thereby achieving fully electrically controlled vertical magnetic moment reversal, which will significantly reduce the power consumption of the device and greatly promote the practical application and integration of SOT devices.
[0021] In order to achieve magnetization reversal more efficiently, we need to find a high SOT The material of the spin current source has become a core task. By changing the composition and thickness of the heavy metal layer as the spin current source, a high SOT efficiency can be achieved. On the other hand, achieving ξ SOT The high efficiency of the controllable switching SOT is the premise of freedom. However, for a specific device composed of a certain material system, its ξ SOT The present invention uses an iron-rhodium alloy layer as a spin source layer, and the magnetic phase transition between different magnetic structures of the iron-rhodium alloy material can be efficiently controlled by temperature and other factors. SOT Sensitivity depends on the magnetic structure, thus achieving SOT Highly efficient regulation. The iron-rhodium alloy has a first-order magnetic phase transition from a low-temperature antiferromagnetic phase to a high-temperature ferromagnetic phase near room temperature, which is reflected in multiple physical quantities such as resistance and specific heat. The change in magnetic structure is also accompanied by the common change of multiple degrees of freedom such as lattice structure and electronic structure. The present invention uses temperature to drive the phase transition of the iron-rhodium alloy and at the same time affects the ξ SOT Carry out efficient regulation.
[0022] In addition, if the full electrically controlled vertical magnetic moment reversal is to be achieved in the vertical magnetization heterojunction based on the iron-rhodium alloy, the spin polarization in the z direction must be introduced; the present invention utilizes the vertical magnetization heterojunction of the iron-rhodium alloy layer / non-magnetic light metal layer / ferromagnetic layer / covering layer to achieve the full electrically controlled vertical magnetic moment reversal. Based on the vertical magnetization heterojunction based on the magnetic phase change material iron-rhodium alloy constructed by the present invention (such as FeRh / Ti / CoFeB / MgO / SiO2 as exemplified in the embodiments below), when the charge flow is introduced into the iron-rhodium alloy spin source layer, a spin flow will be generated, and the first-order phase transition of the iron-rhodium alloy from the antiferromagnetic to the ferromagnetic phase will be induced by changing the system temperature, and the spin-orbit torque efficiency of the system can be controlled during the phase change of the iron-rhodium alloy, especially the spin-orbit torque can be significantly controlled by up to 450% (without the effect of an external auxiliary magnetic field). Since the magnetic phase change material iron-rhodium alloy will undergo an antiferromagnetic-ferromagnetic first-order phase transition as the temperature changes, when the temperature makes the magnetic phase change material iron-rhodium alloy in the antiferromagnetic state, the spin-orbit torque efficiency ξ SOT Higher (can be expressed as ξ SOT_higher ); When the temperature makes the magnetic phase change material iron-rhodium alloy in the ferromagnetic state, the spin-orbit torque efficiency ξ SOT Smaller (can be expressed as ξ SOT_lower ), (ξ SOT_higher -ξ SOT_lower ) / ξ SOT_lower Up to 450% (as described later) Figure 5 When the charge flow is introduced into the iron-rhodium alloy spin source layer, a spin flow is generated, and the temperature drives the spin source to undergo a magnetic phase change, which can realize the system ξ SOT Taking Ti as an example, when the magnetic phase change material iron-rhodium alloy contacts Ti, the spin current flowing through the interface will undergo spin precession to produce spin polarization in the z direction, and in the iron-rhodium alloy system, Fe atoms will generate an effective field in the z direction generated by the 4d metal Rh. Under the action of the above two mechanisms, the fully electrically controlled vertical magnetic moment reversal is achieved in the vertically magnetized heterojunction based on the magnetic phase change iron-rhodium alloy.
[0023] It can be seen that the method of the present invention based on the magnetic phase change material iron-rhodium alloy to achieve significant control of the spin-orbit torque can significantly control the spin-orbit torque of the system (up to 450%) and achieve full electric control of the vertical magnetic moment flipping, which is quite large. SOT The fully electrically controlled vertical magnetic moment reversal makes the magnetic phase change material iron-rhodium alloy an efficient source of spin current generation.
[0024] (3) The present invention uses the spin current generated by the iron-rhodium alloy layer within the phase transition range of the iron-rhodium alloy to achieve a fully electrically controlled vertical magnetic moment flip induced by the spin-orbit torque, making the iron-rhodium alloy an efficient spin current generator and a candidate material for ideal spin electronics devices. The present invention provides a method for opening and closing the "SOT degree of freedom" in real time by controlling the magnetic order state in the iron-rhodium alloy material to achieve effective regulation of the spin-orbit torque efficiency.
[0025] The perpendicular magnetized heterojunction based on the magnetic phase change material iron-rhodium alloy constructed in the present invention provides a new and effective strategy for achieving temperature-driven magnetic phase change and significantly regulating the efficiency of the spin-orbit torque, namely, effectively regulating the performance of the spin-orbit torque device in a dynamic, continuous and reversible manner.
[0026] In summary, the present invention has the following advantages: First, the present invention is based on the magnetic phase change material iron-rhodium alloy as the spin source layer, and changes the temperature to induce the magnetic phase change of the iron-rhodium alloy, that is, the first-order phase transition from antiferromagnetic to ferromagnetic, to obtain the system's ξ SOT The temperature hysteresis behavior is consistent with the magnetic phase transition, and the ξ SOT The result is an increase of about 450%. Secondly, by using the spin current generated by the iron-rhodium alloy layer, the fully electrically controlled vertical magnetic moment reversal is achieved in the temperature range corresponding to the antiferromagnetic and ferromagnetic phases of the iron-rhodium alloy. The present invention compares different methods and the effect of temperature on ξ SOT The regulation of ξ SOT The invention proposes to drive the magnetic phase transition of the spin source layer iron-rhodium alloy by temperature and SOT The realization of significant regulation provides a new and effective strategy to effectively regulate the performance of SOT devices in a dynamic, continuous and reversible manner. The acquisition of high spin-orbit force efficiency is conducive to reducing the power consumption of the device and realizing ultra-high density and ultra-low power information storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the crystal structure of FeRh material based on (001) orientation and the spin structure in ferromagnetic state and antiferromagnetic state in Example 1 of the present invention.
[0028] Figure 2 This is a high-resolution XRD diffraction pattern of the (001) oriented FeRh film formed in Example 1 of the present invention.
[0029] Figure 3 is a curve showing the change of the magnetization intensity M and resistance R of the FeRh material with temperature in Example 1 of the present invention; wherein, Figure 3(a) in the figure corresponds to the curve of magnetization intensity M changing with temperature. Figure 3 (b) in the figure corresponds to the curve of resistance R changing with temperature.
[0030] Figure 4 (a) is a schematic diagram of the structure of a PMA heterojunction based on a (001) oriented FeRh film formed in Example 1 of the present invention and (b) a schematic diagram of a test configuration; wherein, Figure 4 (a) is a schematic diagram of the structure. Figure 4 (b) is a schematic diagram of the test configuration; the Arabic numerals in brackets in the figure represent the thickness of the layer (unit: nm).
[0031] Figure 5 This is the SOT efficiency curve of the FeRh / Ti / CoFeB / MgO / SiO2 sample formed in Example 1 of the present invention measured under a temperature cycle from 200K to 400K.
[0032] Figure 6 This is a measured diagram of the fully electrically controlled vertical magnetic moment reversal of the FeRh / Ti / CoFeB / MgO / SiO2 sample formed in Example 1 of the present invention without an external auxiliary magnetic field.
[0033] Figure 7 This is the measured graph of the fully electrically controlled vertical magnetic moment reversal without an external auxiliary magnetic field, after applying in-plane pre-magnetization fields in different directions (+x and -x) to the FeRh / Ti / CoFeB / MgO / SiO2 sample formed in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0035] The method of the present invention for achieving significant control of spin-orbit torque based on the magnetic phase change material iron-rhodium alloy is as follows: Figure 4 As shown in (a) of FIG. 1 , the magnetic memory comprises: a non-collinear antiferromagnetic layer and a magnetic tunnel junction arranged on the non-collinear antiferromagnetic layer.
[0036] Among them, the spin source is a binary alloy iron-rhodium alloy with an antiferromagnetic-ferromagnetic first-order phase transition, and the sample structure comprises: a non-magnetic light metal layer, a ferromagnetic layer and a covering layer, wherein the ferromagnetic layer has a perpendicular magnetic anisotropy characteristic.
[0037] In a preferred embodiment, the perpendicular magnetization heterojunction selected is a Ti / CoFeB / MgO system, such as Figure 4 As shown in (a) in the figure. The reasons for choosing this perpendicular magnetization heterojunction are as follows: (1) The non-magnetic light metal Ti is used to induce the perpendicular magnetic anisotropy of the ferromagnetic layer CoFeB; (2) Ti has an extremely small spin Hall angle θ≈0.0004, so the contribution of the generated spin-orbit torque effect to the system can be ignored; (3) Ti can be used to isolate the coupling between the in-plane magnetized iron-rhodium alloy layer and the perpendicular magnetization CoFeB; (4) The Ti layer has a high transmittance to the spin current, so the spin current flowing through the Ti layer does not cause significant loss to it, ensuring the accuracy of the spin-orbit torque effect of the measured system; (5) When the spin current flows through the iron-rhodium alloy / Ti interface, spin precession occurs to generate spin polarization in the z direction, thereby breaking the symmetry of the magnetic moment of the CoFeB layer in the z direction, thereby realizing the fully electrically controlled perpendicular magnetic moment reversal.
[0038] In a preferred embodiment, the vertical magnetic layer is a CoFeB alloy, for example: Co 20 Fe 60 B 20 、Co 40 Fe 40 B 20 、Co 60 Fe 20 B 20 In practical applications, the above three ratios of CoFeB alloys can all be used to construct SOT devices and can be flexibly adjusted according to actual application needs.
[0039] In a preferred embodiment, the cover layer material includes any one of MgO / SiN, MgO / Ta, and MgO / SiO2. Among them, SiN, Ta and SiO2 can also be flexibly selected according to actual conditions, and the materials are not limited to the materials listed above.
[0040] In a preferred embodiment, the sample device structure is a Hall target. In practical applications, a cylindrical device structure can also be constructed, which is more conducive to improving its thermal stability, reducing the lateral size of the tunnel junction, and increasing the magnetic storage density. Of course, device structures of various shapes can also be flexibly selected and constructed according to actual needs.
[0041] The following specific embodiments explain the present invention in detail through test data such as the growth of FeRh films, the construction of FeRh / Ti / CoFeB / MgO / SiO2 perpendicular magnetization heterojunctions, the spin-orbit torque effect measured within the FeRh magnetic phase transition range, and the realization of fully electrically controlled perpendicular magnetic moment reversal.
[0042] Example 1
[0043] This embodiment is based on the magnetic phase change material FeRh to construct a perpendicular magnetic heterojunction FeRh / Ti / CoFeB / MgO / SiO2 (such as Figure 4 As shown in FIG. 1 , a single-crystalline FeRh film is first prepared on a MgO substrate, and then a non-magnetic light metal layer (i.e. Figure 4 The Ti shown in the example has a thickness of 3 nm), the ferromagnetic layer (Co 20 Fe 60 B 20 , with a thickness of 1 nm) and a capping layer (i.e. Figure 4 The MgO / SiO2 shown in the example has a thickness of MgO (2nm) / SiO2 (2nm) stacking).
[0044] Among them, the preparation of single-crystalline FeRh thin films is specifically based on ultra-high vacuum magnetron sputtering technology (when the sample is grown, the background vacuum is ≤1×10 –7 Torr), the target material composition is Fe 50 R 50 Alloy, deposit single crystal FeRh film on MgO (001) single crystal substrate. Before sputtering FeRh film, MgO substrate needs to be pre-annealed (600℃, 60min) to remove impurities adsorbed on the substrate surface to achieve secondary cleaning of the substrate, thereby ensuring the growth of a film with less roughness. After pre-annealing, the substrate temperature is kept at 600℃ and the sample holder is rotated to sputter FeRh film. The sputtering pressure is 2mTorr and the sputtering power is 40W (DC). After sputtering is completed, the temperature is raised to 750℃ and maintained for 1.5h for in-situ annealing to improve the crystallization quality of the film. After annealing, the sample is cooled (cooling rate is 30℃ / min) to room temperature to complete the preparation of FeRh film. The thickness of the obtained FeRh film is 4nm.
[0045] For the FeRh / Ti / CoFeB / MgO / SiO2 multilayer film structure, after the FeRh film is sputtered, the Ti / CoFeB / MgO / SiO2 multilayer film is deposited at room temperature. After the sputtering of the Ti / CoFeB / MgO / SiO2 multilayer film is completed, the sample is in-situ annealed (200°C, 30 min) and then cooled to room temperature to obtain a perpendicular magnetic anisotropy system based on the FeRh film.
[0046] Figure 2 This is the high-resolution X-ray diffraction pattern of the MgO (001) / / FeRh sample grown in the present invention. In addition to the (001) diffraction peak of the MgO substrate, the FeRh film only has a (001) diffraction peak, indicating that the obtained FeRh film has a single-phase growth property and grows along the c-axis direction.
[0047] In order to prove that the FeRh film prepared by the present invention has the first-order phase transition behavior from antiferromagnetic to ferromagnetic, the present invention uses a comprehensive physical property test system (PPMS) and a superconducting quantum interference spectrometer (MPMS) to test and characterize its phase transition characteristics from the aspects of magnetic properties and transport properties. Figure 3 As shown, with the increase of temperature, the magnetization of the FeRh film increases from 186emu / cc (room temperature) to 1120emu / cc (400K), which is a typical first-order phase transition characteristic of antiferromagnetism-ferromagnetism. In addition, with the increase of temperature, in addition to the change of magnetism, there is also a change of electronic structure, that is, the ferromagnetic order with heating is also regarded as a decrease in resistance. During the cooling process, the magnetization (resistance) of the FeRh film gradually decreases (increases) to the initial value, with significant thermal hysteresis behavior, indicating that the FeRh film prepared in the present invention has a first-order phase transition characteristic of antiferromagnetism-ferromagnetism.
[0048] In order to study the significant regulation of SOT based on the FeRh magnetic phase transition, the spin-orbit torque in the FeRh phase transition range (200-400K) was tested by harmonic Hall voltage and converted into ξ SOT ,like Figure 5 As shown in Figure 2, when the test temperature drops from 400K to 200K, the FeRh layer is in the antiferromagnetic state (200K). SOT Compared with the ferromagnetic state (400K), the SOT High efficiency regulation up to 450%. Among them, FeRh in the antiferromagnetic and ferromagnetic states obtains high and low SOT efficiencies ξ respectively. SOT , respectively denoted as ξ SOT_higher and SOT_lower In the present invention, the temperature is SOT The control formula is defined as follows: (ξ SOT_higher -ξ SOT_lower ) / ξ SOT_lower The experimental results also confirm that the magnetic phase structure can significantly and continuously regulate the spin-orbit torque effect. More importantly, the FeRh / Ti / CoFeB / MgO multilayer structure has a SOT The temperature adjustability range is achieved within the temperature range near room temperature, which is more valuable and research-significant for the application of SOT devices.
[0049] Figure 6 The SOT-induced magnetization reversal of the FeRh / Ti / CoFeB / MgO / SiO2 multilayer film structure in the FeRh magnetic phase transition range (200-400K) without the in-plane auxiliary magnetic field is given, that is, the fully electrically controlled perpendicular magnetic moment reversal. Figure 4As shown in (b), during the test, a pulse of 200μs given by Keithley 6221 (current source) is applied along the x direction (the length direction of the Hall bar structure), and then a y direction current of 0.1mA with a pulse width of 20ms given by Keithley 2182 is used to detect the Hall voltage of the system, convert the Hall voltage into Hall resistance, and convert the Hall resistance value R at 200, 300 and 400K to H As the test current changes, it is summarized in Figure 6 It should be noted that no in-plane auxiliary magnetic field is applied during the test. In the present invention, three representative temperatures are selected: 400K (FeRh is in a ferromagnetic state), 300K (FeRh is in a ferromagnetic and antiferromagnetic coexistence state) and 200K (FeRh is in an antiferromagnetic state). Figure 6 As shown in Figure 2, the critical reversal current density of the FeRh / Ti / CoFeB / MgO heterojunction decreases with decreasing temperature, which also indicates that FeRh has a stronger ξ in the antiferromagnetic phase. SOT It is worth noting that when the temperature is 200K, the critical reversal current density j of the system s =8.6×10 6 A / cm 2 , which is different from other perpendicular magnetization heterojunctions based on antiferromagnetic materials. s quite.
[0050] In addition, at a temperature of 400K, the change in the magnetic moment of the FeRh layer by applying an external field can also be used to regulate the reversal polarity of the fully electrically controlled field-free reversal. In the experiment, a 2000Oe in-plane magnetic field is first applied along the +x direction to arrange the magnetic moment of the FeRh layer along the external field direction +x, and then the fully electrically controlled vertical magnetic moment reversal is achieved without any in-plane auxiliary magnetic field; then a 2000Oe in-plane magnetic field is applied along the -x direction to arrange the magnetic moment of the FeRh layer along the external field direction -x, and then the fully electrically controlled vertical magnetic moment reversal is achieved without any in-plane auxiliary magnetic field. Figure 7 As shown, applying pre-magnetizing fields in different directions can effectively regulate the polarity of the fully electrically controlled perpendicular magnetic moment reversal of the FeRh / Ti / CoFeB / MgO system.
[0051] In summary, the temperature-driven magnetic phase transition of FeRh has an important effect on ξ SOT The efficient regulation and fully electrically controlled vertical magnetic moment reversal achieved at low current density further confirm the great advantages of FeRh as a spin source in the future development of spin electronics.
[0052] In summary, the present invention provides a method for regulating the effect of an efficient spin-orbit torque, using a magnetic phase change material iron-rhodium alloy as a spin source, realizing efficient regulation of spin-orbit torque and SOT-induced deterministic vertical magnetization reversal without external field assistance through magnetic phase change, so that iron-rhodium alloy becomes a candidate material for efficient spin current generation source and ideal spin electronics device. The phenomenon of effective regulation of SOT intensity is achieved by controlling its magnetic ordered state in a specific material, and a method for opening and closing "SOT degrees of freedom" in real time is provided. The realization of temperature-driven magnetic phase change and significant regulation of SOT efficiency provides a new and effective strategy, that is, SOT device performance is effectively regulated in a dynamic, continuous and reversible manner. Moreover, compared to ordinary heavy metals, the low critical reversal current density also indicates that the power consumption of SOT devices will be greatly reduced, thereby achieving high-density, low-power, and efficient magnetic information storage.
[0053] The above embodiments are only examples. For example, the non-magnetic light metal layer, the ferromagnetic layer and the covering layer may also be made of other known materials, and the thickness may also be flexibly adjusted. For example, in addition to the binary alloy FeRh with standard composition as illustrated in the above embodiments, the present invention is also applicable to iron-rhodium alloys with other Fe:Rh atomic ratios. As long as they behave as magnetic phase change materials, the spin-orbit torque efficiency can be regulated, but there will be slight differences in the regulation range.
[0054] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A heterojunction based on a magnetic phase change material iron-rhodium alloy, having a Hall target structure, characterized in that: It comprises a magnetic phase change material iron-rhodium alloy layer and a non-magnetic light metal layer, a ferromagnetic layer and a covering layer which are stacked in sequence from bottom to top on the iron-rhodium alloy layer, wherein the ferromagnetic layer has a perpendicular magnetic anisotropy characteristic; The iron-rhodium alloy layer serves as a spin source layer, and the magnetic phase change material iron-rhodium alloy can undergo an antiferromagnetic-ferromagnetic first-order phase transition as the temperature changes.
2. The heterojunction constructed based on the magnetic phase change material iron-rhodium alloy as claimed in claim 1, characterized in that: The non-magnetic light metal layer is a Ti layer; Preferably, the thickness of the iron-rhodium alloy layer is 4 to 6 nm.
3. The heterojunction constructed based on the magnetic phase change material iron-rhodium alloy as claimed in claim 1, characterized in that: The material used for the ferromagnetic layer includes Co 20 Fe 60 B 20 、Co 40 Fe 40 B 20 、Co 60 Fe 20 B 20 Any one of .
4. The heterojunction constructed based on the magnetic phase change material iron-rhodium alloy as claimed in claim 1, characterized in that: The covering layer is any one of a MgO / SiN stack, a MgO / Ta stack, and a MgO / SiO2 stack, and the MgO layer in the stack is closer to the iron-rhodium alloy layer than the other layer.
5. A method for regulating spin-orbit torque using a heterojunction constructed based on a magnetic phase change material iron-rhodium alloy as claimed in any one of claims 1 to 4, characterized in that: A charge flow is introduced into the spin source layer, and the magnetic phase change material iron-rhodium alloy undergoes a first-order phase transition from antiferromagnetic to ferromagnetic by changing the temperature; When the temperature makes the magnetic phase change material iron-rhodium alloy in the antiferromagnetic state, the spin-orbit torque efficiency ξ SOT Higher; When the temperature makes the magnetic phase change material iron-rhodium alloy in the ferromagnetic state, the spin-orbit torque efficiency ξ SOT Smaller.
6. The method according to claim 5, characterized in that The temperature variation range is 200K~400K.
7. The method according to claim 5, characterized in that Let the spin-orbit torque efficiency ξ SOT The higher value is ξ SOT_higher , spin-orbit torque efficiency ξ SOT The smaller value is ξ SOT_lower , then (ξ SOT_higher -ξ SOT_lower ) / ξ SOT_lower Not less than 450%.